Feasibility Study on Shore-based Treatment Technology of Ship's Ballast. Issue 1 (January 2021) - Zhang, Kailei; Chu, Qiang; Liu, Liankun; Jia, Jianna
Abstract: The International Convention on the Control and Management of Ballast Water and Sediment on Ships officially entered into force for our country on January 22, 2019. The Convention stipulates a series of requirements for the compliant discharge of ballast water. Compared with the ship's own ballast water treatment facility, the ballast water bank-based treatment facility has the advantages of economy, environmental protection, and stability. In order to improve my country's ability to implement the Ballast Water Convention and promote the construction of my country's green ports, discussion and research on ballast water bank-based treatment technologies are necessary. This article describes the main methods of receiving and processing ship's ballast on water and shore, analyzes the prospects and existing problems of receiving and processing ballast on water and on shore, and puts forward relevant suggestions for research on ballast water and shore treatment technology.